Animal and plant disease and pest monitoring for the Caribbean Region. Proceedings of a regional workshop - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The document explains that this workshop was an early step in the implementation of a four year project to improve the monitoring of animal and plant diseases in the Caribbean. Funding for the project is provided by the Canadian International Development Agency (CIDA) and IICA as part of a program announced in August, 1987, at the Ninth Inter-American Conference of Ministers of Agriculture in Ottawa. Funding under this program will provide training, computers, scientific expertise and personel to manage the project. It adds that considering that this was the first combined meeting of national Directors of animal and plant protection programs of thirteen countries in the Caribbean, the workshop made remarkable progress in setting the direction and priorities for the project. Session I introduced the project and its economic and social relevance to the Caribbean. In Session II, the stage for our discussions was set by excellent reviews of the state of the art of disease and pest monitoring in the Americas. The important message was that we must start small and define our goals as clearly as possible, a difficult task given the many diverse interests in this field. Sessions III and IV reviewed current disease and pest monitoring activities in the Caribbean and provided a forum for the group to consider recommendations on the project's direction and priorities. The closing Session V produced five recommendations, an Advisory Committee to guide the project, and lists of priority plant and animal health topics for initial attention. The first broad objective is to improve regional expertise and investigative capability through training, a newsletter, networking activities, the provision of consulting expertise, computer equipment and software, and the creation of a reginal centre to provide ongoing support in the region. The second broad objective is to develop a region-wide surveillance system by building on previous disease and pest reporting initiatives.